Causality between Capital Investment in the Tourism Sector and Tourist Arrivals in ASEAN - NONTHAPOT, Sakkarin (Journal of Advanced Research in Law and Economics; Vol 8 No 8 (2017): JARLE, Volume VIII, Issue 8(30), Winter 2017DO - 10.14505//jarle.v8.8(30).22, 2018)
This study investigates the causal relationship between capital investment in the tourism sector and international tourist arrivals to ASEAN countries. The study employs panel data which includes annual data from 10 countries over the period 1995 to 2016. The results reveal that between capital investment in the tourism sector and international tourist arrivals there is bi-directional long-run causality. ASEAN countries should increase the budget for the supporting tourism investment continuously and should target tourism promotion as an entire region.to attract international tourists to visit ASEAN and to encourage the expansion of tourism revenue .